Organocatalytic regio-, diastereo- and enantioselective γ-additions of isoxazol-5(4H)-ones to β, γ-alkynyl-α-imino esters for the synthesis of axially chiral tetrasubstituted α-amino allenoates. Issue 6 (27th January 2021) - Li, Fushuai; Liang, Shuai; Luan, Yepeng; Chen, Xuling; Zhao, Hanhui; Huang, Anqi; Li, Pengfei; Li, Wenjun
Abstract : The chiral phosphoric acid catalyzed regio-, diastereo- and enantioselective reaction of isoxazol-5(4 H )-ones with β, γ-alkynyl-α-imino esters has been developed. Abstract : The chiral phosphoric acid catalyzed regio-, diastereo- and enantioselective reaction of isoxazol-5(4 H )-ones with β, γ-alkynyl-α-imino esters has been developed. With the established methodology, γ-addition of β, γ-alkynyl-α-imino esters and C -allenylation of isoxazol-5(4 H )-ones were achieved with high regio- and stereoselectivities, affording diverse α-imino allenoates featuring an adjacent quaternary carbon stereocenter and an axially chiral tetrasubstituted allene motif in high yields.